A Comparative Study to Evaluate the Body Mass Index in Urban and Rural School Children of Belagavi - Premalata Rotti; Virabhadrayya Kulkarni (Rajiv Gandhi University of Health Sciences, 2024)
Introduction Body mass index BMI is a simple tool used to screen body weight and assess whether the body weight is healthy for your body size. In the post COVID-19 era a new normal has been established. A high BMI augments the risk of various health hazards. In developing countries both obesity and undernutrition in children is a burning issue.Objective The current cross-sectional study was conducted to assess the BMI of urban and rural school children and to compare their BMI.Methodology Five schools were selected 3 urban and 2 rural and a total of 1191 students from these schools were screened and assessed for their BMI.Results On comparison urban school boys were more underweight 85 than rural school boys 79 while among rural and urban school girls urban school girls were more underweight 77 than rural school girls 63. Among urban school girls 3294 1.02 were obese while among rural school girls 1195 0.5 was obese. About 68454 14.9 urban boys 50248 20 rural boys 65294 22 urban girls and 70195 36 rural girls showed healthy weight BMI.Conclusion Unlike the common concern about obesity in Indian school children this study indicates that underweight is more prevalent especially among urban school children boys and girls compared to rural school children.